Adverse Events Relating to Prolonged Hard Collar Immobilisation: A Systematic Review and Meta-Analysis. Issue 8 (October 2022) - Brannigan, Jamie F.M.; Dohle, Esmee; Critchley, Giles R.; Trivedi, Rikin; Laing, Rodney J.; Davies, Benjamin M.
Study Design: Systematic review and meta-analysis. Objective: To evaluate systematically the complications of prolonged cervical immobilisation in a hard collar. Methods: Following registration with PROSPERO, a systematic search of electronic databases (MEDLINE, EMBASE) was conducted. Two reviewers independently screened the search results according to pre-determined search criteria. Data was extracted and tabulated. Joanna Briggs Institute checklists were used for assessing the quality of included studies. Results: The search identified 773 articles. A total of 25 studies were selected for final inclusion. The results largely comprised a mixture of case reports/series, cohort studies and reviews. The most commonly reported complications were pressure ulcers, dysphagia and increased intracranial pressure. A pressure ulcer pooled prevalence of 7% was calculated. There was insufficient data for quantitative analysis of any other complication. Conclusions: There is significant morbidity from prolonged hard collar immobilisation, even amongst younger patients. Whilst based upon limited and low-quality evidence, these findings, combined with the low-quality evidence for the efficacy of hard collars, highlights a knowledge gap for future research.